Law and its Masters. The legal Transformations in the Neoliberal Order - Giolo, Orsetta (Soft Power, 2024)
For neoliberalism, the law is not merely a technique to be used to maximise results: it is one of its main instruments of implementation. The neoliberal ideology, in fact, seeks forms of protection through law, which, as will be better explained below, seems to take on the same dichotomous logic stigmatised by Judith Butler with reference to contemporary power dynamics (Butler, 2015). This, in order, on the one hand, to promote all that and all those who tend to conform to neoliberal planning and, on the other hand, to repress those who do not conform and challenge it. This means that within neoliberal practices particular attention is paid to the legal phenomenon and its articulation, with the aim of making law itself consistent with the aims of neoliberalism (Dardot & Laval, 2017).